The Scholarship of Teaching and Learning In and Across the Disciplines - Chick, Nancy L., 1968-; McKinney, Kathleen (Book collections on Project MUSE., 2013)
The scholarship of teaching and learning (SoTL) began primarily as a discipline-based movement, committed to exploring the signature pedagogical and learning styles of each discipline within higher education, with little exchange across disciplines. As the field has developed, new questions have arisen concerning cross-disciplinary comparison and learning in multidisciplinary settings This volume, written by a group of experts, provides a state-of-the-field review of SoTL scholarship within a range of disciplines and offers a stimulating discussion of critical issues related to interdisciplinarity in teaching, learning, and SoTL research.